PEMBERDAYAAN MASYARAKAT DALAM UPAYA PENGEMBANGAN DESA WISATA DI DESA GESIKAN, KECAMATAN PAKEL, KABUPATEN TULUNGAGUNG - Putranto, Anggoro; Ratnaningrum, Dyah Ayu (Social Landscape Journal, 2023)
The research discusses the empowering role of local communities in developing tourist villages which has an impact on the welfare of the community. The tourism sector is an alternative that can be used as an effort to improve welfare through community empowerment. The Plumpung Park tourist attraction, which is based on potential, is managed by local communities in the Gesikan Village area, Pakel District, Tulungagung Regency, which is an application of community empowerment in tourist villages. The aim of this research is (1) to describe the supporting and inhibiting factors of the Plumpung Garden Tourism Village, (2) to describe the role of the community in developing Plumpung Gaarden tourism. This study used descriptive qualitative method. The research results show (1) the existence of factors inhibiting and supporting the development of Tourism Villages. Supporting factors can be maximized to minimize existing obstacles and weaknesses of the village. (2) Management of tourist villages requires the participation and concern of local communities for the development of tourist village areas as well as providing creative ideas and innovations for the development of these tourist village areas. Supporting facilities in tourist villages also have an important role in providing benefits to visitors. Regarding development in the Taman Plumpung tourist village, it is still in the development process which is not yet optimal, so there is still development that must be carried out on an ongoing basis. Through community empowerment in tourist villages, it is hoped that it can sustainably improve the welfare of the community.